Dexamethasone added to induction and post-remission therapy in older patients with newly diagnosed acute myeloid leukemia: a multicenter, phase II trial (DEXAML-02) - Sarah Bertoli; Emilie Bérard; Pierre Peterlin; Romain Guieze; Yohan Desbrosses; Yosr Hicheri; Omar Benbrahim; Martin Carre; Corentin Orvain; Anne Banos; Marc Bernard; Emmanuel Gyan; et al. (Haematologica)
Not available.